Konsep Dasar Sistem Informasi Manajemen - Hany Maria Valentine; Lira Arum Kusumaning Thyas (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Management Information Systems (MIS) are an important component in modern organizational operations which function to manage, process and disseminate information to support decision making, planning and control. This article discusses the basic concepts of MIS, including its definition, components and functions in an organizational context. MIS consists of hardware, software, data, procedures and human resources that interact to produce relevant and accurate information. The key role of MIS in improving operational efficiency, simplifying business processes, and providing timely reports to managers is explored in depth. In addition, this article also discusses the latest challenges and trends in MIS development, including issues of data security, system integration, and adoption of new technologies. Through a deep understanding of the basic concepts of MIS, organizations can more effectively utilize information technology to achieve their strategic goals.